Anisotropic Kirchhoff pre-stack depth migration at the COSC-1 borehole, central Sweden. Issue 1 (24th June 2019) - Simon, H; Buske, S; Hedin, P; Juhlin, C; Krauß, F; Giese, R
SUMMARY: A remarkably well preserved representation of a deeply eroded Palaeozoic orogen is found in the Scandinavian Caledonides, formed by the collision of the two palaeocontinents Baltica and Laurentia. Today, after 400 Ma of erosion along with uplift and extension during the opening of the North Atlantic Ocean, the geological structures in central western Sweden comprise far transported allochthonous units, the underlying Precambrian crystalline basement, and a shallow west-dipping décollement that separates the two and is associated with a thin layer of Cambrian black shales. These structures, in particular the Seve Nappes (upper part of the Middle Allochthons), the Lower Allochthons and the highly reflective basement are the target of the two approximately 2.5 km deep fully cored scientific boreholes in central Sweden that are part of the project COSC (Collisional Orogeny in the Scandinavian Caledonides). Thus, a continuous 5 km tectonostratigraphic profile through the Caledonian nappes into Baltica's basement will be recovered. The first borehole, COSC-1, was successfully drilled in 2014 and revealed a thick section of the seismically highly reflective Lower Seve Nappe. The Seve Nappe Complex, mainly consisting of felsic gneisses and mafic amphibolites, appears to be highly anisotropic. To allow for extrapolation of findings from core analysis and downhole logging to the structures around the borehole, several surface and borehole seismic experiments were conducted. Here, we use three long offset surface seismic profiles that are centred on the borehole COSC-1 to image the structures in the vicinity of the borehole and below it. We applied Kirchhoff pre-stack depth migration, taking into account the seismic anisotropy in the Seve Nappe Complex. We calculated Green's functions using an anisotropic eikonal solver for a VTI (transversely isotropic with vertical axis of symmetry) velocity model, which was previously derived by the analysis of VSP (Vertical Seismic Profile) and surface seismic data. We show, that the anisotropic results are superior to the corresponding isotropic depth migration. The reflections appear significantly more continuous and better focused. The depth imaging of the long offset profiles provides a link between a high-resolution 3-D data set and the regional scale 2-D COSC Seismic Profile and complements these data sets, especially in the deeper parts below the borehole. However, many of the reflective structures can be observed in the different data sets. Most of the dominant reflections imaged originate below the bottom of the borehole and are situated within the Precambrian basement or at the transition zones between Middle and Lower Allochthons and the basement. The origin of the deeper reflections remains enigmatic, possibly representing dolerite intrusions or deformation zones of Caledonian or pre-Caledonian age.